Stability Analysis of a Two-Patch Competition Model with Dispersal Delays - Guowei Sun; Ali Mai (Discrete Dynamics in Nature and Society)
In this paper, we study a Lotka-Volterra competition model with two competing species moving randomly between two identical patches. A constant dispersal delay is incorporated into the dispersal process for each species. We show that the dispersal delays do not affect the stability and instability of all four symmetric equilibria. Numerical simulations are presented to demonstrate the effect of dispersal delays on the stability and instability of the symmetric coexistence equilibrium.